Manajemen Pendayagunaan Dana Zakat Oleh Baznas Dalam Mengentaskan Kemiskinan Di Kabupaten Lebak - Latif, Ahmad Latif (Jurnal Ilmiah Ekonomi Islam, 2024)
The Gini Index for Indonesia rose from 0.381 to 0.388 in March 2023. The issue of poverty also remains a concern, impacting roughly 25.90 million people or 9.36% of the total population. To address this problem, Baznas Lebak Regency has adopted a policy in line with Regional Regulation No. 11 of 2005 article 17. The policy focuses on adherence to religious regulations, prioritizing mustahik (eligible recipients), and seeks input from local government. The Revolving Capital Fund program at Baznas Lebak is supported by infaq and sadaqah funds, adhering to the principles of Islamic fiqh, instead of zakat funds. Baznas Lebak is positioned in quadrant V for program development, with an EFI total score of 2.68 and an EFE total score of 2.59.